Peran Teknologi Informasi Dalam Meningkatkan Transparansi dan Akuntabilitas Pemerintah Daerah Kota Bengkulu - Yamanda, Shasy Eka; Marianata, Anita (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Abstract This research discusses the role of information technology in enhancing transparency and accountability in the local government of Bengkulu City. In the rapidly advancing digital era, information technology has become an essential element in various aspects of life, including in governance. Local government. The purpose of this research is to understand how the role of information technology enhances transparency and accountability in the local government of Bengkulu City. The research method used is descriptive qualitative research. Descriptive qualitative research is a type of research that employs contemporary or modern data collection techniques, where data is gathered and analyzed using a descriptive approach to understand social phenomena and governance processes related to the use of information technology; the qualitative approach is the appropriate method. This research concludes that the Bengkulu city government is implementing the use of this information technology by running e-government in the form of a service portal that can be accessed through a website on the internet.